Laboratory testing for lupus anticoagulant (LA) in patients taking direct oral anticoagulants (DOACs): potential for false positives and false negatives - Favaloro, Emmanuel J.; Mohammed, Soma; Curnow, Jennifer; Pasalic, Leonardo (Pathology, 2019)
We and others have previously highlighted the potential problems with testing of lupus anticoagulants (LA) in patients on anticoagulant therapy, including most recently as related to the direct oral anticoagulants (DOACs). Thus, current DOACs in use (e.g., dabigatran, a direct thrombin inhibitor, and apixaban and rivaroxaban, both direct Xa inhibitors), affect a wide variety of coagulation assays, including those used in LA investigation. The Russell viper venom time (RVVT) assay in particular, key to the investigation of LA, is highly sensitive to DOACs. LA is a marker of thrombophilia, and patients who have had a thrombosis may be placed on a DOAC. Thus, there is a high likelihood that LA testing will be requested on patients whilst they are on DOACs. In the current report, we have assessed data from our facility for the past two and a half years for all LA tests performed by RVVT testing, and have evaluated this data with respect to patient anticoagulant status. In total, there were 7170 test requests for RVVT associated testing during the period of data capture. Most LA-RVVT screen results (5008; ∼70%) were within normal limits, thereby excluding LA by RVVT method in most of the patient cohort. All DOACs led to a prolongation in both RVVT screen and confirm assays. However, rivaroxaban affected the screen more than the confirm, leading to higher RVVT ratios, whereas apixaban affected the confirm more than the screen, leading to lower RVVT ratios. LA testing in the presence of DOACs also led to lower intra-patient consistency in LA test results. We conclude that ex-vivo data appears to confirm the potential for false positive (with rivaroxaban) and potential for false negative (with apixaban) identification of LA in patients on DOAC treatment. We also make some recommendations in regards to such testing.